What Is “Personality”? An Underexamined Paragraph in Spinoza - Adler, Jacob (Revista Conatus - Filosofia de Spinoza (ISSN 1981-7509), 2019)
Um exame do significado da palavra “personalidade” na Parte 2, Capítulo 8, Parágrafo 1 da Cogitata Metaphysica de Spinoza. Abstract An examination of the meaning of the word “personality” in Part 2, Chapter 8, Paragraph 1 of Spinoza’s Cogitata Metaphysica.